Caribbean Report 23-05-1990 - Crosskill, Hugh (anchor); Charles, Eugenia (interviewee); Croes, Rudy (interviewee); Jones, Mark (analyst); Woodroffe, Colin (interviewee); Persaud, Vishnu (interviewee); Goffe, Leslie (correspondent); Martin, Lionel (correspondent); Carmichael, Stokely; Strickland, William (interviewee) (The British Broadcasting Corporation, 1990)
As Dominica prepares for general elections next Monday, the leaders and representatives of the Organization of Eastern Caribbean States are in Dominica for their bi-annual meeting. Michael Douglas, the Opposition Leader, criticises Prime Minister, Eugenia Charles, for hosting the meeting so close to the elections. However, Eugenia Charles says that the close proximity of the two events poses no problems and provides further comments on the price of bananas and the Antiguan arms scandal. Secondly, seventy-seven political parties from seventy countries were represented at the Socialist International Conference in Cairo, Egypt whilst the only Caribbean delegate was the MEP party of Aruba. Following the Financial News, international scientists at the Royal Geographical Society in London announce that global warming could lead to a rise in sea levels and to devastation to coastal areas in the Caribbean. One of the scientists noted that since North America and Europe are the main contributors of global warming they should bear the economic cost of combating the greenhouse effect and not the Caribbean islands. The report concludes with the attendance of black scholars from the United States and other countries at a symposium in Havana, Cuba on the life and works of Malcolm X.
1. Headlines (00:00-00:40)
2. Host Dominican Prime Minister, Eugenia Charles, states that Antigua's arms scandal will not be on the agenda at the OECS Summit. Hugh Crosskill interviews Eugenia Charles (00:41-04:17)
3. Only one Caribbean political party represented at the Socialist International Conference in Cairo, Egypt. Hugh Crosskill interviews Rudy Croes of the MEP party of Aruba (04:18-07:15)
4. Financial News. Mark Jones of the BBC Financial Unit comments on oil prices on the world market (07:16-08:38)
Keywords: Elections -- Dominica; O.E.C.S. (Organization) -- Congresses; Global warming -- Caribbean Area; Coast changes -- Caribbean Area; Global warming -- Economic aspects; X, Malcolm, 1925-1965; Race relations -- Congresses; Race discrimination; Arms transfers -- Antigua; Socialist International Conference; MEP Party -- Aruba